Adaptation of the STARR test for adult Italian population: A speech test for a realistic estimate in real-life listening conditions. (2nd April 2016) - Dincer D'Alessandro, Hilal; Ballantyne, Deborah; De Seta, Elio; Musacchio, Angela; Mancini, Patrizia
Abstract: Objectives : To introduce the Italian adaptation of the STARR test based on a roving-level adaptive method to mimic challenging real-life listening conditions for use in people with auditory prostheses. Design : Normative data were collected and interlist-variability, as well as learning effects, were investigated using a within-subject design with repeated measures. Study sample : A group of 32 normal-hearing (NH) adults participated in the study. Results : The average speech reception threshold (SRT) for NH subjects was −8.4 dB SNR. The variability of mean SRTs across test lists was relatively small (≤1 dB for all test lists). The statistically significant differences between lists were eliminated after applying correction factors. On the basis of variability for the corrected SRTs within each subject, a difference of 2.8 dB in SRT was meaningful for outcome comparisons using one test list per condition and 2 dB using two lists per condition. Statistical analysis did not show any significant learning effects. Conclusions : Findings in NH listeners suggested that the Italian STARR test could be a promising supplement to existing speech assessment tools. Further studies in populations with hearing impairment could contribute to cross-language studies.